The aim of this research is to obtain characteristics of composite biofiber textile prepared using 10% chitosan as base material with addition of polyvinyl alcohol at various levels of 20%, 22%, 24% and 26% (w/v) by wet spinning process. Stages of the study included solution formulation, viscosity solution measurement, wet spnining process and formation the biofiber composite textile, the last measurement of chemical and physical characteristics of biofiber composite textile such as tensile stre - Bambang Riyanto; Ruddy Suwandi; Ikhwan Dimas Permana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2010)
The aim of this research is to obtain characteristics of composite biofiber textile prepared using 10% chitosan as base material with addition of polyvinyl alcohol at various levels of 20%, 22%, 24% and 26% (w/v) by wet spinning process. Stages of the study included solution formulation, viscosity solution measurement, wet spnining process and formation the biofiber composite textile, the last measurement of chemical and physical characteristics of biofiber composite textile such as tensile strength, the percentage of elongation at break and fourier transform infrared spectrophotometry (FTIR). The viscosity values of biofiber composite textile solution are 4,08 ± 0,00 cP - 5,43 ± 0,00 cP; the obtained biofiber composite has pale yellow colour with alkali smell and has appearance like rope with diameter for each ranges about 1,60 ± 0,08 mm - 1,50 ± 0,16 mm. The physical characteristics such as tensile strenght was 16,23 ± 2,23 cN - 24,05 ± 0,87 cN and percentage of elongation at break were 15,08 ± 1,04%-18,72 ± 0,93%. Chemical interaction between functional group of chitosan and polyvinyl alcohol indicated by the changes in the value of NH2 long wave group of chitosan at the peak of spectrophotometric reading.